Detecting Indications of Financial Statement Fraud: a Hexagon Fraud Theory Approach - Tarjo; Alexander Anggono; Eklamsia Sakti (AKRUAL: JURNAL AKUNTANSI, 2021)
This study emphasizes on examining the fraud hexagon theory referring to signs of fraud of financial statements, which employs all manufacturing companies listed in the IDX (Indonesia Stock Exchange). However, total selected sample are 153 of the manufacturing industry. The companies are categorized into indicated and not indicated committing fraud in the 2010-2018 period by applying the Beneish M-Score. The findings demonstrated that financial stability, the financial targets, the external pressures, the nature of industry, and CEO duality can be applied to predict fraud of financial statements. Meanwhile, personal financial needs, ineffective monitoring, quality of external auditors, auditor turnover, director turnover, and marginal costs cannot indicate occurrence of the fraud of financial statement. The findings conclude that pressure, ego, and opportunity significantly affect the financial statement fraud. Future research are suggested to consider different proxies for fraudulent financial statements; hence, the accuracy of the proxies can be compared with this study. Moreover, adding other proxies of conspiracy such as bonuses received by managers will be beneficial.